ä¸å›½è€å¸ˆå¯¹ä¸¹æˆŽå¸ƒæ‹‰å¤§å¦å¸ˆèŒƒæ•™è‚²å¦é™¢æ±‰è¯æ•™è‚²ä¸“ä¸š2022å±Šå¦ç”Ÿ å¦ä¹ æ±‰è¯çš„å½±å“ - Novita, Sela; Veronica, Tjen; Afrimonika, Yoanna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
In learning Chinese language, the teacher also plays a very important role. In the learning process, the FKIP UNTAN Chinese Language Education Study Program is taught by local lecturers and also taught by Native lecturers who were brought in from China to teach. The learning methods by native lecturers and local lecturers are different, the influence of the learning is also different. To find out the influence of native lecturers on students' learning of Chinese language, the author conducted research on students of the Class of 2022 of the Chinese language Education Study Program, FKIP UNTAN.The aim of this research is to determine the influence of native lecturers on Chinese language learning for students of the Class of 2022 Chinese Language Education Study Program, FKIP UNTAN, and to find out the learning methods used by native lecturers. This research uses qualitative data analysis methods. The author uses the questionnaire method, observation method and interview method.The research results show that the learning methods used by native lecturers are direct methods, object methods, demonstration methods, translation methods, and game methods. The research results showed that the influence of students learning Chinese Language with native lecturers was very strong (136 points). Students felt that native lecturers had a big influence on their pronunciation, vocabulary mastery, listening ability and Mandarin speaking ability. Therefore, native lecturers can have a big influence on Chinese language learning for Class of 2022 students at the Chinese Language Education Study Program, FKIP UNTAN.